Lo real y el coro: ¿parodia o juego con una convención? - Szymoniak, Ewelina (Romanica Silesiana)
In Lo real (2001) by Belén Gopegui, a novel treating of relations between an individual and the capitalist society, a special character is revived, namely the chorus. While confronting the role it plays in the Spanish novel under analysis using the theories of the functions of the chorus as a constitutent of ancient tragedy, we answer the question whether the writer’s act of introducing this collective character to a comtemporary prose work should be treated as a parody or as playing with a commonly known literary convention, aimed to achieve specific objectives. The discussion touches on, for instance, the concept of the chorus as an interlude, a rightful participant in the plot, ethical authority, a literary “extension” of the author, an ideal reader etc. Key words: Contemporary Spanish prose, Greek tragedy, chorus, Belén Gopegui.